Pengaruh Penggunaan Media Zoom Cloud Meeting terhadap Peningkatan Hasil Belajar Alquran Hadits pada Masa Pandemi Covid-19 Siswa Kelas Iv Mi As’adiyah Bontang Tahun Pembelajaran 2020/2021 - Murni; Maghfiroh, Lailatul (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
The online learning (distance learning) conducted by the teachers of MI As'adiyah Bontang for the subjects of Quran Hadith is by using Zoom Cloud Meeting media. The research problem formulated by the researcher is: